2019
DOI: 10.1029/2019jd030513
|View full text |Cite
|
Sign up to set email alerts
|

Toward Large‐Eddy Simulations of Dust Devils of Observed Intensity: Effects of Grid Spacing, Background Wind, and Surface Heterogeneities

Abstract: Dust devils are convective vortices with a vertical axis of rotation made visible by lifted soil particles. Currently, there is great uncertainty about the extent to which dust devils contribute to the atmospheric aerosol input and thereby influence Earth's radiation budget. Past efforts to quantify the aerosol transport and study their formation, maintenance, and statistics using large‐eddy simulation (LES) have been of limited success. Therefore, some important features of dust devil‐like vortices simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(56 citation statements)
references
References 50 publications
14
42
0
Order By: Relevance
“…This was also found in the high‐resolution terrestrial LES by Giersch et al. (2019): low‐wind conditions favor more long‐lasting vortices than high‐wind conditions.…”
Section: Comparison With Large‐eddy Simulationssupporting
confidence: 75%
See 1 more Smart Citation
“…This was also found in the high‐resolution terrestrial LES by Giersch et al. (2019): low‐wind conditions favor more long‐lasting vortices than high‐wind conditions.…”
Section: Comparison With Large‐eddy Simulationssupporting
confidence: 75%
“…A typical pressure field predicted by LES is shown in Figure 13, with localized vortex-induced pressure drops forming at the intersection of larger scale convective cells (Kanak, 2006;Michaels & Rafkin, 2004;Spiga et al, 2016;Toigo & Richardson, 2003). It should be emphasized here that the results we discuss in this study with our 25-m LES will be in need to be confirmed by future work using higher resolution LES (typically 5 m, a factor of 5 better) to better resolve the population of small-radius vortices (Giersch et al, 2019;Nishizawa et al, 2016).…”
Section: Comparison With Large-eddy Simulationsmentioning
confidence: 63%
“…The number of vortex tracks decreases with increasing lifetime and the lifetime distribution indicates a relatively strong positive skew, which is typical for dust devil statistics derived from observations and numerical simulations (e.g., Giersch et al, 2019;R. Lorenz, 2011;R.…”
Section: Accepted Articlementioning
confidence: 68%
“…It is defined as the distance at which the absolute pressure drop is reduced to 50 % of the core pressure. For further details on dust devil track analysis, the reader is referred to Giersch et al (2019).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation